Comparisons of Ion Density From IVM With the GNSS Differential TEC‐Derived Electron Density on the FORMOSAT‐7/COSMIC‐2 Mission. Issue 8 (11th August 2022) - Wu, Qian; Pedatella, Nicholas M.; Braun, John J.; Schreiner, William; Weiss, Jan; Chou, Min‐Yang; Zakharenkova, Irina; Cherniak, Iurii; Hunt, Douglas; Heelis, Roderick; Vanhove, Teresa
Abstract: We report on a new method to derive the on‐orbit electron density using the Tri Global Navigation Satellite System (GNSS) Radio‐occultation System (Tri‐GNSS Radio occultation System (TGRS)) differential total electron content data and compare it to the Constellation Observing System for Meteorology Ionosphere and Climate‐2 Ion Velocity Meter (IVM) ion density data. We found that the IVM ion density is about 8%–15% lower than the TGRS derived density at the insertion orbit (∼710 km) and 5% higher at the mission operation orbit (∼540 km) for reasons that are currently unknown. Using a linear coefficient, we scaled the IVM data to remove the offset between TGRS‐derived electron density and the IVM ion density for the two orbital heights. We believe the scaled IVM densities eliminate any inter‐spacecraft discrepancy, making the IVM data suitable for use in high precision multi‐satellite scientific investigations of longitudinal and local time variations of non‐migrating tides, planetary waves and space weather operational applications. Key Points: A new method is described to derive the on orbit electron density using the differential Global Navigation Satellite System (GNSS) slant data and compared with the FORMOSAT‐7/Constellation Observing System for Meteorology Ionosphere and Climate‐2 ion velocity meter (IVM) ion density data IVM ion density was smaller (larger) than the GNSS‐derived electron density at high (low) orbits A linear scaling is applied to the IVM ion density to consistently align the IVM‐derived plasma densities with those derived from the TGRS